Source Mechanism of Seismic Explosion Signals at Santiaguito Volcano, Guatemala: New Insights From Seismic Analysis and Numerical Modeling - Rohnacher, Alicia; Rietbrock, Andreas; Gottschämmer, Ellen; Carter, William; Lavallée, Yan; De Angelis, Silvio; Kendrick, Jackie E.; Chigna, Gustavo (Frontiers in Earth Science, 2021)
Volcanic activity at the Santiaguito dome complex (Guatemala) is characterized by lava effusion interspersed with small, regular, gas-and-ash explosions that are believed to result from shallow magma fragmentation; yet, their triggering mechanisms remain debated. Here, we use data from a permanent seismic and infrasound network established in 2018 and additional temporary stations, including a seismic array, deployed during a 13-day field investigation in January 2019 to analyse and resolve the source characteristics of fragmentation leading to gas-and-ash explosions. Seismic data gathered within a distance of 4.5 km from the vent show a weak seismic signal 2-6 s prior to the explosions and associated main seismic signal. To resolve the source location and origin of the seismic signals, we first used ambient noise analysis to assess seismic velocities in the subsurface and then used two-dimensional spectral element modelling (SPECFEM2D) to simulate seismic waveforms. The analysed data revealed a two-layer structure beneath the array, with a shallow, low-velocity layer (vs=650 m/s) above deeper, high-velocity rocks (vs=2650 m/s). Using this velocity structure, possible source mechanisms and depths were constrained using array and particle motion analyses. The comparison of simulated and observed seismic data indicated that the precursory signal is associated with particle motion in the RZ-plane pointing towards the opening of tensile cracks at a depth of ~600 m below the summit; in contrast, the main signal is accompanied by a vertical single force, originating at a shallow depth of about ~200 m. This suggests that the volcanic explosions at Santiaguito are following a bottom-up process in which tensile fractures develop at depth and enable rapid gas rise which leads to the subsequent explosion. The result indicates that explosions at Santiaguito do not occur from a single source location, but from a series of processes possibly associated with magma rupture, gas channeling and accumulation, and fragmentation.